Bimetallic and plasmonic Ag-Au on TiO2 for solar water splitting : an active nanocomposite for entire visible light region absorption - Patra, Kshirodra K.; Gopinath, Chinnakonda S. (Chemcatchem, 2016)
The current study demonstrates a potential method for maximum utilization of the entire visible light region of the solar spectrum by designing a plasmonic-metals semiconductor composite. A combination of Ag+Au nanoclusters would broaden the visible-light absorption at least between 400 and 650nm. This hypothesis was evaluated through solar water splitting (SWS) activity of Au-TiO2, Ag-TiO2, and Ag on Au-TiO2 (AgAuT) composites. AgAuT bimetallic nanocomposite shows the maximum apparent quantum yield of 3.3% with hydrogen generation (718molh.g(-1)) from aqueous methanol, and overall water splitting activity (7molg.h(-1), AQY=0.04%) under one sun conditions. Enhanced photocatalytic activity of AgAuT is partly attributed to the formation of hot electrons. A thin layer of Ag coating on Au particles leads to a core-shell morphology with Au in the core. Fermi level equilibration between metal and titania, and Schottky junction formation are directly demonstrated. The strong electronic interaction between Ag and Au, and with TiO2 is evident from its electron rich character and confirmed by Raman spectroscopy, X-ray photoelectron spectroscopy, photoluminescence, and high-resolution TEM measurements. Electronic factors seem to be responsible for the high rate of hydrogen production.

Baby step in assembling and integrating the components of an artificial photosynthesis device with forced heterojunctions towards improved efficiency - Salgaonkar, Kranti N.; Bajpai, Himanshu; Mhamane, Nitin B.; Nalajala, Naresh; Chauhan, Inderjeet; Thakkar, Kavita; Joshi, Kavita; Gopinath, Chinnakonda S. (Journal of Materials Chemistry A, 2023)
How to achieve unassisted, economical, scalable, and sustainable artificial photosynthesis for liquid fuels/products with improved solar-to-fuel efficiency (STFE) to address a carbon-neutral economy remains a big question. To a large degree, the extent of charge separation at heterojunction interfaces and charge utilization determine the STFE. Towards this, BiVO3 is assembled from ionic-precursors into TiO2 pores, and integrated structurally and electronically with TiO2 on calcination as BiVO4 quantum dots (BVQDs). BVQDs in TiO2 (BVT) pores lead to an all-inorganic system with a sub-quadrillion number of heterojunctions in a 1 cm(2) device (contains similar to 25 mu g of BiVO4 (similar to 2.5 wt%) in the nanopores of similar to 975 mu g of TiO2 (similar to 97.5 wt%)) and facilitate artificial photosynthesis. We demonstrate 31-38% STFE with a photon to chemical conversion turn over frequency (ToF(P2C)) of 2.73 s(-1) with a 1 cm(2) wireless BiVO4-TiO2 artificial leaf (BVT-AL) device for HCHO and CH3OH. The sequential nature of CO2 reduction to HCHO and then to CH3OH is evident from the reaction results. (CO2)-C-13 isotopic labeling experiments confirm that the input CO2 is the source for product formation. A large increase in the photocurrent density and incident photon-to-current efficiency (IPCE) of BVT, over 100% for the BiVO4 photoanode in visible light, demonstrates and supports efficient visible light absorption, charge separation and migration to the redox sites. A device has been demonstrated to show sustainable activity in direct sunlight, and addresses scalability from 1 to 9 cm(2). Assuming no change (50% decrease) in the STFE, a 6.74 m(2) device is expected to convert 1 (0.5) kg h(-1) CO2 into C1-oxygenates in sunlight. DFT calculations carried out with anatase TiO2 (101) and BiVO4 (121) interfaces support many of the experimental findings, including electron flow from the latter to the former, and interaction of the oxygen of TiO2 with BiVO4 and vice versa at the interface towards forced heterojunctions.

Bimetallic and plasmonic Ag and Cu integrated TiO2 thin films for enhanced solar hydrogen production in direct sunlight - Mani, Sunesh S.; Rajendran, Sivaraj; Arun, Pushkaran S.; Vijaykumar, Aparna; Mathew, Thomas; Gopinath, Chinnakonda S. (Energy Advances, 2024)
<div class="abstract author" id="aep-abstract-id7" style="box-sizing: border-box; margin: 0px 0px 8px; padding: 0px; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;"> Plasmonic metal nanoparticle-integrated mesoporous TiO2 nanocomposites (Ag/TiO2, Cu/TiO2 and Ag–Cu/TiO2), prepared by a simple chemical reduction method, have been demonstrated to show superior activity in thin-film form for solar H2 generation in sunlight. Integration of Ag + Cu on TiO2 significantly enhances the solar H2 production due to the combined SPR effect of both metal species and the possible synergistic interaction among Cu + Ag in Ag–Cu/TiO2. TiAgCu-1 (0.75 wt% Ag and 0.25 wt% Cu on TiO2) showed the highest H2 yield of 6.67 mmol h−1 g−1 and it is 43 times higher than that of bare TiO2. The thin-film form of TiAgCu-1 shows 5 times higher solar H2 production than its powder counterpart. 1 wt% of Ag or Cu on TiO2 shows a H2 yield of 4.6 or 2 mmol h−1 g−1, respectively, which underscores the importance of combined or synergistic effects. The increase in solar H2 generation in Ag–Cu/TiO2 is attributed to factors such as the SPR effect of Cu and Ag, and strong interaction between Ag and Cu. The high photocatalytic efficiency of the TiAgCu-1 thin film is attributed to the large dispersion of metallic species with relatively high Ag/Cu surface atomic ratio, enhanced light absorption, a heterogeneous distribution of Ag and Cu species, and high double layer capacitance. The inter particle mesoporous network increases the interfacial charge transfer and reduces the mass transfer limitations. The plausible photocatalytic reaction mechanism could involve the combination of direct electron transfer from metal (Cu/Ag) to TiO2 as well as the significant field effect due to the Ag–Cu alloy, which is expected to increase the electron excitation locally. <div class="abstract graphical" id="aep-abstract-id9" style="box-sizing: border-box; margin: 0px 0px 8px; padding: 0px; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;"> Plasmonic metal nanoparticle integrated mesoporous TiO2 nanocomposites (Ag/TiO2, Cu/TiO2 and Ag–Cu/TiO2), prepared by a simple chemical reduction method, have been demonstrated to show superior activity in thin-film form for solar H2 generation.